Improvement of the technology of fatty acids obtaining from oil and fat production waste - Kalyna, Viktoriia; Stankevych, Serhii; Myronenko, Liliia; Hrechko, Andrii; Bogatov, Oleg; Bragin, Oleksandr; Romanov, Oleksii; Ogurtsov, Yuriy; Semenov, Evgeny; Filenko, Olesya (Eastern-European Journal of Enterprise Technologies, 2022)
Fatty acids are an important component in the pharmaceutical, food, chemical industries. The production of various types of products requires a certain purity and quality of fatty acids. To obtain these compounds, it is promising to use soapstocks, which are waste products of alkaline refining of oils. The peculiarity of the work lies in determining the effect of the process parameters of soapstock decomposition with sulfuric acid on the saponification number, which is an important production characteristic of fatty acids. The study used sunflower soapstock according to DSTU 5033 (CAS 68952-95-4) with a mass fraction of total fat of 69.5 %, fatty acids – 64.5 %. The soapstock was treated with a sulfuric acid solution at a temperature of 90 °C, the process duration was 40 min. Rational parameters of soapstock treatment were determined: concentration of sulfuric acid in the reaction mass is 80 %, concentration of an aqueous solution of sulfuric acid – 50 %. In the experiment interval, the settling duration of the reaction mass does not affect the saponification number of fatty acids. The settling time of 1 hour is effective for the isolation of fatty acids. Under these conditions, the saponification number of fatty acids was 186.4 mg KOH/g. The acids correspond to fatty acids of the first grade according to DSTU 4860 (CAS 61788-66-7): mass fraction of moisture and volatile substances – 1.2 %, mass fraction of total fat – 97.5 %, cleavage depth – 95.0 % oleic acid. The obtained data allow rational and most efficient use of the reagent – sulfuric acid. The results of the work make it possible to reduce the duration of fatty acids obtaining from soapstocks, since the efficiency of the process with the minimum duration of mass settling has been confirmed. The improved technology of soapstock decomposition makes it possible to obtain a valuable product – high-quality fatty acids under rational conditions